2022
DOI: 10.3389/fmicb.2021.776862
|View full text |Cite
|
Sign up to set email alerts
|

The Bacterial and Fungal Microbiota of “Robiola di Roccaverano” Protected Designation of Origin Raw Milk Cheese

Abstract: Robiola di Roccaverano is an artisanal Protected Designation of Origin (PDO) soft cheese made with raw goat’s milk and by the addition of Natural Milk Culture (NMC) to drive the fermentation process. Cheeses collected from five different dairy plants were analyzed for their bacterial and fungal microbiota diversity. Lactococcus lactis and Leuconostoc mesenteroides were the main bacterial population, while Galactomyces candidum and Kluyveromyces marxianus constituted the core mycobiota but many other minor taxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…Here, the major shaping of the microbial consortia occurred in the very early stages of the cheese production, and a relatively stable microbiota composition was reported over the next 26 weeks of ageing [18]. Another recent study on raw goat cheese ripened for 5-15 days reported a stable microbiota composition, again supporting the notion of a slow-but-continuous shaping of the microbial consortia [19].…”
Section: Discussionsupporting
confidence: 70%
“…Here, the major shaping of the microbial consortia occurred in the very early stages of the cheese production, and a relatively stable microbiota composition was reported over the next 26 weeks of ageing [18]. Another recent study on raw goat cheese ripened for 5-15 days reported a stable microbiota composition, again supporting the notion of a slow-but-continuous shaping of the microbial consortia [19].…”
Section: Discussionsupporting
confidence: 70%
“…Here, major shaping of the microbial consortia occurred in the very early stages of the cheese production and a rather stable microbiota composition is reported over the next 26 weeks of ageing [30]. Another recent study on 5-15 days of ripened raw goat cheese reported a stable microbiota composition, supporting the view of a slow-but-continuous shaping of the microbial consortia [31].…”
Section: Discussionsupporting
confidence: 71%
“…However, Corbo et al [ 69 ] remarked the predominance of Y. lipolytica in ewe’s milk, which is characterized by a higher fat content than cow’s and goat’s milk. As for Wickerhamiella pararugosa (synonym Candida pararugosa ), this yeast has recently been found among the minority species in various dairy products [ 13 , 70 , 71 ] and milk [ 72 ]. Air is considered the main contamination source of Cladosporium spp.…”
Section: Discussionmentioning
confidence: 99%